Effects of feeding low levels of crude glycerin with or without other by-products on performance and carcass characteristics of feedlot heifers - Schneider, C.J.; Parsons, G.L.; Miller, K.A.; Thompson, L.K.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Expansion of the renewable fuels industries has increased availability of by-products that are well suited for use as cattle feed. Glycerin is among the principal by-products of biodiesel production, comprising approximately 10% (by weight) of the soybean oil that is used to manufacture soy-based diesel fuel. Our previous research evaluated effects of including between 0% and 16% glycerin in flaked-corn finishing diets and revealed that optimal growth performance was achieved with 2% glycerin addition. Our laboratory experiments have suggested that even lower levels of glycerin may be effective at stimulating digestion. Therefore, the objective of this study was to evaluate effects of low levels of glycerin in the diet on performance and carcass characteristics of finishing cattle. Furthermore, because distillers grains and other by-products are increasingly common in feedlot rations, we opted to evaluate glycerin in corn-based finishing diets as well as in diets that consisted of a combination of corn grain, distillers grains, and soybean hulls.
Keywords: Beef; Crude glycerin; Performance; Carcass characteristics; Feedlot; Heifers